Respon Kailaan (Brassica oleraceae L.) Terhadap Media Tanam Dan POC Nasa Pada Sistem Vertikultur - Dhone, Emiliyani Meo; Astutik, Astutik; Sutoyo, Sutoyo (Fakultas Pertanian, 2018)
Efforts that can be mode to increase the production of crops on narrow land by using chaff charcoal and POC Nasa composition. The objective of this research is to know the effect of charcoal charcoal on growth media and application of NASA liquid organic fertilizer to the production of kailaan plants. This research uses factorial RAK consisting of 3 replications. Factor I is the dose of charcoal husk (A) that is: A0 = 0 kg, A1 = 0.5 kg of charcoal husk and A2 = 1 kg of husk charcoal. Factor II is a dosage of POC Nasa (N) consisting of 3 levels, namely : N0 = 0 ml/l water, N1 = 5 ml/l water and N2 = 10 ml/l water. The analysis was analyzed statistically using F test, if the result of the variance were significantly different (F arithmetic> F table), then to compare the two treatment treatments was done by the advanced test with the BNT's Smallest Differential Test of 5% level. The result of this research can be concluded that there is interaction between husk husk and POC Nasa dose to leaf area at age 2 and 6 weeks. The best growth of kuta was obtained on the treatment of 0.5 kg/paralon husk husk and the dosage of POC Nasa 10 ml/L water showed the highest yield of leaf at 6 weeks at 684,00cm2. The best kailaan result was obtained from 0.5 kg/paralon husk husk (44.37 g/plant) and Nasa 5-10 ml/L water dose (41,22-42,63 g/plant). The best kailaan result was obtained from 0.5 kg/paralon husk husk (44.37 g/plant) and Nasa 5-10 ml/L water dose (41,22-42,63 g/plant). Usaha yang dapat dilakukan untuk meningkatkan produksi tanaman pada lahan sempit dengan menggunakna komposisi arang sekam dan POC nasa. Penelitian bertujuan untuk mengetahui dampak penggunaan arang sekam pada media pertumbuhan dan aplikasi pupuk organik cair NASA terhadap produksi tanaman kailaan. Penelitian ini menggunakan RAK faktorial yang terdiri atas 3 ulangan. Faktor I adalah takaran arang sekam (A) yaitu : A0 = 0 kg, A1 = 0,5 kg arang sekam dan A2 = 1 kg arang sekam. Faktor II adalah dosis POC Nasa (N) terdiri dari 3 taraf, yaitu : N0 = 0 ml/l air, N1 = 5 ml/l air dan N2 = 10 ml/l air. Analisis dianalisis secara statistik menggunakan uji F, apabila hasil ragam berbeda nyata (F hitung > F tabel), maka untuk membandingkan dua rata-rata perlakuan dilakukan uji lanjut dengan Uji Beda Nyata Terkecil BNT taraf 5%. Hasil penelitian dapat disimpulkan bahwa terdapat interaksi antara arang sekam dan dosis Nasa terhadap luas daun umur 2 dan 6 minggu. Pertumbuhan kailaan terbaik diperoleh pada arang sekam 0,5 kg/paralon sebesar 343,72 cm2 ditindai pada luas daun dan diawali hasil interaksi serta dosis Nasa 10 ml/L air terhadap luas daun umur 6 minggu dengan luas daun sebesar 264,86 cm2. Hasil tanaman kailaan terbaik diperoleh pada penambahan arang sekam 0,5 kg/paralon (44,37 g/tanaman) dan dosis Nasa 5-10 ml/L air (41,22-42,63 g/tanaman).